The COMT val158met polymorphism in ultra-endurance athletes - van Breda, K.; Collins, M.; Stein, D. J.; Rauch, L. (Physiology & Behavior, 2015)
Chronic levels of physical activity have been associated with increased dopamine (D2) receptors resulting in increased sensitivity to dopamine release. The catechol-O-methyltransferase enzyme, responsible for dopamine degradation, contains a functional polymorphism, which plays an important role in dopamine regulation within the prefrontal cortex. This polymorphism has previously been shown to affect human cognition and personality. However, the effect of this polymorphism has not been shown in ultra-endurance athletes.